Evaluation of Kasturba Gandhi Balika Vidyalaya in Assam with Special Reference to its Management - Gogoi, Sampreety (Prabandhan: Indian Journal of Management, 2015)
The Kasturba Gandhi Balika Vidyalaya (KGBV) scheme was introduced by the Government of India in August 2004, then integrated in the Sarva Shiksha Abhiyan program, to provide educational facilities for girls belonging to scheduled castes, scheduled tribes, other backward classes, minority communities, and families below the poverty line in educationally backward blocks in India. The present study presented a detailed analysis of the management system of the Kasturba Gandi Balika Vidyalaya (KGBV). The findings of the study revealed that the monitoring from different sources was not satisfactory. Therefore, convergence with different organizations and schemes is to be developed for strengthening the Kasturba Gandi Balika Vidyalaya and also for proper implementation of the programme.